Why governments may opt for financial repression policies: selective credits and endogenous growth. Issue 1 (1st January 2017) - Yülek, Murat A.
Abstract: Financial repression policies (lowering real interest rates, selective credits and other restrictions on financial markets, products and institutions) have been widely discussed in the economic literature during the last four decades. A key question is 'why governments would opt for financial repression policies in the first place'? As an answer, governments' desire to obtain rents from the financial system or to manage public debt servicing have been suggested as the typical underlying incentives. It has been argued in 1970s and 1980s that especially in developing economies, financial repression would have negative consequences on economic growth and financial development, although more recently financial repression policies are back as governments in the developed economies aim at obtaining low-cost funds from the financial markets in the aftermath of the global financial crises.In this article, a simple two-sector model is set up in order to show that governments may institute financial repression policies to internalise production and investment externalities. It is shown that such a government policy is welfare improving and abolishment of selective credits may cause welfare loss. The model also provides a case where financial policy is designed according to the priorities of industrial policy.